Evaluation Over the Implementation of the No-Smoking Policy in Pariaman City Transportation Office: A Qualitative Study - Dhea Synthia; Tri Krianto (Universitas Muhammadiyah Palu, 2025)
Introduction: The Pariaman City Government has tried to reduce the number of smokers and the number of people exposed to cigarette smoke by issuing several policies, one of which is the policy regarding the No Smoking Area (KTR) which is contained in the Pariaman City Regional Regulation Number 9 of 2017 concerning No Smoking Areas. This study aims to evaluate the implementation of the implementation of the No Smoking Area at the Office of the Transportation Agency of Pariaman City. Methods: This research uses a qualitative study, with data collection through in-depth interviews and observations with an evaluation study design. The informants of this study were 7 people, namely 2 from the Health Office of Pariaman City and 5 from the Transportation Office of Pariaman City, taken using purposive sampling method. Results: The result of this study is that the implementation of the implementation of the No Smoking Area (KTR) at the Pariaman City Transportation Office is still not going well. As there are still employees who smoke in the room, there has been uneven socialisation and monitoring from the Health Office for KTR at the Pariaman City Transportation Office, to the lack of strict sanctions for those who violate the rules in the No Smoking Area (KTR). Conclusion: In conclusion, our study contributes to evaluating implementation of No Smoking Area (KTR) at the Pariaman city Transportation Office. This research provides insights into the implementation of No Smoking Area (KTR) is still not good enough, so it’s necessary to improve the monitoring and evaluation of this program in the the Pariaman city Transportation Office. Future studies should expand the scope of the research site so that it can describe boarder conditions, which in turn will advancing knowledge in the field of health.